Results comparison of cervical cancer early detection using cerviray ® with VIA test - Ali Budi Harsono; Hadi Susiarno; Dodi Suardi; Kemala Isnainiasih Mantilidewi; Viko Duvadilan Wibowo; Yudi Mulyana Hidayat (BMC Research Notes)
Abstract Objectives This study investigates the performance of artificial intelligence (AI) technology, namely Cerviray AI®, compared with Cerviray® expert, aiming to compare its sensitivity, specificity, positive predictive value (PPV), and area under the receiver operating characteristic curve (AUC ROC). The Visual Inspection with Acetic Acid (VIA) test is used as the gold standard. Results The study involved 44 patients from various health centers in West Java Province. Performance of Cerviray AI®, or Cerviray® expert, and lastly VIA tests were compared in their ability to detect pre-cancerous cervical lesions in high-risk women of childbearing age. The current study indicated that Cerviray AI® had a sensitivity of 42.9%, specificity of 100%, PPV of 100%, and ROC AUC values of 71.4%. In comparison, the evaluation of the Cerviray® expert demonstrated a sensitivity of 71.4%, specificity of 97.3%, PPV of 83.3%, and ROC AUC values of 84.4%. In conclusion, the evaluation of Cerviray® expert outperformed Cerviray AI® in ROC AUC values. Trial registration Clinical Trials.gov Identifier NCT06518070 Retrospectively registered.